PROFIL KORBAN KEKERASAN TERHADAP ANAK DI KOTA PEKANBARU - Della Putri; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Child abuse is the treatment of an adult or an elderly child by the use of power or authority over a defenseless child who should be the responbility of a parent or caregiver who results in suffering, misery. Children are often victims of violence. Be it school, where they play, even within their own family environment, which should be their place of refuge. Violence experienced by children vary, there is physical and psychological violence. In riau province area there are still many violent acts againts children one of them in pekanbaru city. Cases of victims of violence againts children is actually much more than has been recorded because the victim did not report the case. The purpose of this study is to find out (1) how the social larar of victims of violence against children. (2) factors causing violence againts children. The research was conducted in pekanbaru city with descriptive qualitative research method, where the informants in this study amounted to 4 people, who are considered to have experienced violence against children is diverse. There are physical, psychological, and sexual abuse.Keywords: violence, sexual